Middle Palaeolithic find spots with Nubian cores from the Southern Negev and the Arava, Israel. (2017) - Goder-Goldberger, Mae; Ginat, Hanan; Ragolski, Gidon; Seri, Gregory; Abadi, Itay
No abstract available